The Influence of the Syrup Type on Rheology, Color Differences, Water Activity, and Nutritional and Sensory Aspects of High-Protein Bars for Sportsmen - Jan Małecki; Igor Tomasevic; Bartosz G. Sołowiej (Journal of Food Quality)
Most often, high-protein bars consist of a protein preparation in the form of a loose powder, stuck together with a syrup mixture, ensuring a stable mass. According to the legal regulations in force, at least 20% of the energy value must come from protein for the product to be called high-protein. The objective of this study was to evaluate the impact of different syrup sources (oligofructose, maltitol, tapioca fiber, and chickpea-maize fiber) on rheology, water activity, color, and nutritional and sensorial properties of high-protein bars. Texture has changed depending on the type of syrup used. A significant increase of the hardness parameter referring to the control sample was noted for bars containing chickpea-maize liquid fiber in chocolate (311.65 N), with low adhesiveness simultaneously (54.71 N). Samples without chocolate made with the use of oligofructose syrup had apparently higher dynamic viscosities than other bars (226.67 mPas · g/cm3). The water activity of all tested bars indicated the high stability of samples over time (<0.80), except for samples without chocolate made of PM syrup. The color of the tested bars was from light cream to Earth yellow. Bars obtained with tapioca liquid fiber had the lowest nutritional value. Results presented in this study suggest that selecting the correct type of syrup may significantly influence the functional properties of high-protein bars.